2019
DOI: 10.1002/hbe2.143
|View full text |Cite
|
Sign up to set email alerts
|

Impact of adolescent media multitasking on cognition and driving safety

Abstract: Adolescence is a critical period in brain development particularly in regions related to attention and executive function (EF). As the use of electronics and media in daily activities increases, one essential question is how adolescent attention development and related executive and speed processes are impacted by media multitasking (MM), or the simultaneous use of media (e.g., text messaging while watching television). This review examines current literature concerning (a) the prevalence of MM during adolesce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 74 publications
0
2
0
Order By: Relevance
“…The prevalence of advanced digital devices leads to the increasing occurrence of multitasking [77]. Mokhtari et al [78] collected a survey from 935 undergrad-uate college students to explore students' multitasking habits while they were learning.…”
Section: Multitaskingmentioning
confidence: 99%
“…The prevalence of advanced digital devices leads to the increasing occurrence of multitasking [77]. Mokhtari et al [78] collected a survey from 935 undergrad-uate college students to explore students' multitasking habits while they were learning.…”
Section: Multitaskingmentioning
confidence: 99%
“…Multitasking, defined in the current study, includes both simultaneous multitasking (Xu & Wang, 2018), such as listening to music while doing homework, and serial multitasking, such as switching back and forth between checking social media and reading a book. Investigations in the United States have shown that media activities are the most popular second tasks, such as listening to music, watching TV, using social media, and texting while performing other activities (Common Sense Census, 2015; Stavrinos et al, 2019).…”
Section: Introductionmentioning
confidence: 99%